Hepatogenesis of murine induced pluripotent stem cells in 3D micro-cavitary hydrogel system for liver regeneration - Koh, Mei Shan (2014)
Currently, the only effective option to treat end stage liver disease is orthopedic liver transplantation. Yet, millions of patient died while waiting for suitable hepatocyte tissue donations. The rise of iPSC technology acts as a potential method to obtain autologous hepatocyte tissues. In this study, we aim to combine iPSC technology with 3D scaffolding system to fabricate hepatic tissues for therapeutic uses by performing hepatogenesis of murine iPSC in MCG system. MCG is an interconnected porous scaffold where higher surface area to volume ratio and better perfusion of nutrients into the system was observed. This system will be utilized as a continuous platform for both EB formation and differentiation just by the change of media formulas. From Day 0 to Day 10, the cells will undergo EB formation process, where pluripotent markers will be maintained. It was observed that MCG system generally produced larger EB than non-MCG system. Upon reaching suitable size at Day 10, media formula will be changed at different time points to encourage endodermal induction, hepatic induction, hepatoblast maturation and hepatocyte maintainence respectively. It was observed that hepatocyte functionality was higher in the MCG system. This result demonstrates the potential and success of hepatogenesis in MCG system, which may assist in future research in liver tissue engineering ans iPSC technology.